Legal Challenges of PT Industri Nabati Lestari in Stabilizing National Cooking Oil Prices through the Minyakita Program: An Analysis of Price Increases Exceeding the Highest Retail Price - Tarigan, Klaudius Epikuri Loga; Sukarja, Detania; Robert, Robert (Ultimate Journal of Legal Studies, 2024)
This study examines the phenomenon of price increases in Minyakita, a government-sponsored affordable cooking oil program, which have exceeded the Highest Retail Price (HET) set under Ministry of Trade Regulation No. 18 of 2024. The Minyakita program, involving PT Industri Nabati Lestari (INL), was introduced to stabilize national cooking oil prices and ensure consumer protection. However, field observations indicate distribution violations, hoarding practices, and sales above the regulated HET. This research analyzes the legal aspects of the Domestic Market Obligation (DMO), the effectiveness of HET regulation from the perspective of consumer protection under Law No. 8 of 1999, and the legal measures available to PT INL in addressing the challenges associated with implementing the Minyakita program. The study adopts a normative-empirical legal research method using statutory, conceptual, and case approaches. The findings reveal that the HET policy has not been fully effective due to fluctuating CPO prices and high production costs, which impose significant financial burdens on producers. Consequently, a more realistic adjustment of the HET is necessary, alongside stronger enforcement mechanisms against distribution violations and the optimization of digital monitoring systems such as SIMIRAH. These measures are crucial to achieving a balance between producer interests and consumer protection.